1993
DOI: 10.1002/1097-0142(19930715)72:2<389::aid-cncr2820720213>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopy in pleural malignant mesothelioma: A prospective study of 188 consecutive patients. Part 1: Diagnosis

Abstract: Background. To compare the diagnostic value of thoracoscopic biopsy, fluid cytology, and Abrams needle biopsy, the authors analyzed prospectively the records of 188 patients with malignant pleural mesothelioma examined between 1973 and 1990. Symptoms were pleural effusion in 173 patients, empyema in 1, spontaneous pneumothorax in 1, and radiologic tumor without effusion in 13. Methods. Thoracoscopy was performed using a rigid thoracoscope under local anesthesia with neuroleptanalgesia. A total of 10–20 biopsie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
133
0
18

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(154 citation statements)
references
References 22 publications
3
133
0
18
Order By: Relevance
“…The French nonrandomised series and subsequent randomised trial used higher energy 12 -15 MeV electrons (Boutin and Rey, 1993;Boutin et al, 1995), while the British study employed 140-or 250-kV photons (Low et al, 1995). These alternative radiations give a higher dose beyond approximately 3 cm depth in tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The French nonrandomised series and subsequent randomised trial used higher energy 12 -15 MeV electrons (Boutin and Rey, 1993;Boutin et al, 1995), while the British study employed 140-or 250-kV photons (Low et al, 1995). These alternative radiations give a higher dose beyond approximately 3 cm depth in tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These subcutaneous masses are often symptomatic and refractory to radiotherapy (RT) (Davis et al, 1994). Two nonrandomised series and one randomised controlled trial have demonstrated that a prophylactic three-fraction course of RT reduces the procedure tract metastasis rate to 0% (Boutin and Rey, 1993;Boutin et al, 1995;Low et al, 1995). Recent reviews and guidelines recommended prophylactic radiotherapy following thoracic procedures (BTSSCC, 2001;Parker and Neville, 2003).…”
mentioning
confidence: 99%
“…Diversos autores han reconocido el escaso valor del examen citológico del líquido pleural para establecer el diagnósti-co de MM, 3,18,20,21 pues han calculado una sensibilidad diagnóstica de aproximadamente 26%.…”
Section: Discussionunclassified
“…Este estudio notificó una sensibilidad de 26% para el examen citológico del líquido pleural, y de 21% para la biopsia pleural cerrada, con una sensibilidad acumulativa entre los dos procedimientos tan sólo de 38.7%; asimismo, se atribuyó al material obtenido por toracoscopía una sensibilidad diagnóstica de 80%. 20 Nuestros hallazgos concuerdan con lo notificado en estas series.…”
Section: Discussionunclassified
“…rado, a toracoscopia aumenta o rendimento diagnóstico e resultados de até 95% de positividade já foram relatados na literatura (45) . A toracoscopia é uma técnica invasiva, mas com baixos índices de mortalidade (< 0,01%) (46) .…”
Section: Broncofibroscopiaunclassified